Functionally Designed Nanovaccines against SARS-CoV-2 and Its Variants - Yue Xi; Rongrong Ma; Shuo Li; Gang Liu; Chao Liu (Vaccines, 2024)
COVID-19, generated by SARS-CoV-2, has significantly affected healthcare systems worldwide. The epidemic has highlighted the urgent need for vaccine development. Besides the conventional vaccination models, which include live-attenuated, recombinant protein, and inactivated vaccines, nanovaccines present a distinct opportunity to progress vaccine research and offer convenient alternatives. This review highlights the many widely used nanoparticle vaccine vectors, outlines their benefits and drawbacks, and examines recent developments in nanoparticle vaccines to prevent SARS-CoV-2. It also offers a thorough overview of the many advantages of nanoparticle vaccines, including an enhanced host immune response, multivalent antigen delivery, and efficient drug delivery. The main objective is to provide a reference for the development of innovative antiviral vaccines.